2023
DOI: 10.1051/swsc/2023025
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence of thermospheric wind and composition changes and the resulting ionospheric disturbances in the European sector during extreme geomagnetic storms

Jeongheon Kim,
Young-Sil Kwak,
Changsup Lee
et al.

Abstract: On November 1st and 2nd, 2021, four Halo coronal mass ejections were ejected from the Sun, releasing billions of tons of high-energy particles into interplanetary space. These were directed towards the Earth and reached our planet on November 3rd and 4th, 2021, generating the first G3-level extreme geomagnetic storm since the beginning of the 25th solar cycle. In this study, we investigate the thermospheric and ionospheric responses in the European sector to a G3-level storm using various observational data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…tween westward winds and the development of EPBs [76]. Further, Loutfi et al [77 Malki et al [78] revealed that the equatorward wind varies between 100 and 200 m/ ing the geomagnetic storms at a middle latitude with a time lag in reaching distur from middle to low latitudes [79]. The exact time of triggering of R-T instability ov western longitudes (~70°-80°W) is difficult to determine due to the unavailability of and neutral winds data at low latitudes.…”
Section: On the Enhancement/suppression Of Ionospheric Irregularitiesmentioning
confidence: 99%
“…tween westward winds and the development of EPBs [76]. Further, Loutfi et al [77 Malki et al [78] revealed that the equatorward wind varies between 100 and 200 m/ ing the geomagnetic storms at a middle latitude with a time lag in reaching distur from middle to low latitudes [79]. The exact time of triggering of R-T instability ov western longitudes (~70°-80°W) is difficult to determine due to the unavailability of and neutral winds data at low latitudes.…”
Section: On the Enhancement/suppression Of Ionospheric Irregularitiesmentioning
confidence: 99%